Kinetic study of the microwave-induced thermal degradation of cv. Arbequina olive oils flavored with lemon verbena essential oil - Cherif, Marwa (2021)
The effect of typical domestic microwave heating (015min, at 800W) on the thermal degradation of unflavored and flavored olive oils' minor bioactive compounds and related antioxidant activity was studied. Olive oils from cv. Arbequina were flavored with lemon verbena essential oil (0%, 0.2% and 0.4%, w/w) leading to a linear increase of total phenols (112160 mg gallic acid kg1 oil, R-Pearson=+0.9870), total carotenoids (2.192.56 mg lutein kg1 oil, R-Pearson=+0.9611), and, to a less extent, of chlorophyll (2.323.19 mg pheophytin kg1 oil, R-Pearson=+0.8238). However, no such linear trend was observed for the oxidative stability (6.57.8 h) or the radical scavenging activity (inhibition rates: 40%43%). The contents of total phenols, total carotenoids, and chlorophyll decreased with the rise of the microwave heating time, following their thermal degradation, a second-order kinetic model (0.8784R-Pearson0.9926). The essential oil addition did not influence the estimated second-order rate reaction constants of total phenols (0.000700.00072kg oil min1 mg1 gallic acid)and total carotenoids (0.140.17kg oil min1 mg1 lutein), with a broader variation observed for chlorophyll (0.0140.022kg oil min1 mg1 pheophytin). Globally, total carotenoids degraded faster than total phenols and chlorophyll (half-life of 2.33.4, 8.812.8, and 14.530.8 min, respectively). Moreover, except for chlorophyll, the half-life of total phenols and carotenoids linearly decreased with the essential oil addition (R-Pearson: 0.9999 and 0.9421, respectively), showing that flavoring did not have a protective effect against degradation when subjected to a microwave heating.